UMPSA distributes 2,000 packs of Bubur Lambuk and 500 packs of Gulai Kawah for community iftar - Siti Nur Azwin, Ibrahim (UMPSA, 2024)
KUANTAN, 21 March 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) organized the UMPSA Bubur Lambuk Cooking programme, distributing over 2,000 packs of bubur lambuk and 500 packs of gulai kawah to the local community at the grounds of the Sultan Ahmad 1 Mosque in Kuantan.